2014
DOI: 10.9734/jsrr/2014/10266
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Profile of Heat-processed Canarium schweinfurthii Pulp

Abstract: Amino acid composition of a plant food is an indicator of its protein quality. This could be altered by the processing method. Processed fruit of Canarium schweinfurthii, a Bursereceae, is common traditional snacking item in Nigeria. The pulp of raw and macerated samples of C. schweinfurthii were dried, ground into powders and analyzed for protein and amino acid contents using standard methods. The pulp of raw and macerated samples contain all the amino acids found naturally in plant protein. Glu (6.72-9.03g/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The minimum threshold index of C-PER for good quality protein was reported to be 1.50 [10]. Plant proteins that have been noted to be of good quality in this regard include those from groundnuts: C-PER = 2.62 [55], pigeon pea: C-PER = 1.82 [56], raw and heat-treated fruits of Canarium schweinfurthii (African elemi): C-PER = 1.69-2.10 [57], and millet ogi: C-PER = 1.62 [58]. Therefore, the findings of the present study did not qualify proteins from cassava and yam peels to be of good quality by virtue of their C-PER indices.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum threshold index of C-PER for good quality protein was reported to be 1.50 [10]. Plant proteins that have been noted to be of good quality in this regard include those from groundnuts: C-PER = 2.62 [55], pigeon pea: C-PER = 1.82 [56], raw and heat-treated fruits of Canarium schweinfurthii (African elemi): C-PER = 1.69-2.10 [57], and millet ogi: C-PER = 1.62 [58]. Therefore, the findings of the present study did not qualify proteins from cassava and yam peels to be of good quality by virtue of their C-PER indices.…”
Section: Discussionmentioning
confidence: 99%
“…Fruits of African elemi were obtained from Ngwa road market Aba, Aba South Local Government Area, Abia State, Nigeria. The fruits were processed as described by Anyalogbu et al (2014). The researchers stated that best eaten tenderness of the pulp was achieved by macerating the fruits for 30 min in water (55°C).…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…The flours of AE 0 , AE 15 , AE 30 , and AE 45 based on protein contents (g/100 g sample) of 14.60 ± 0.51, 13.20 ± 1.00, 12.59 ± 0.87, and 12.56 ± 1.10, respectively reported by Anyalogbu et al (2014), were used in formulating feed for the experimental animals as shown in Table 1. The samples were added in the diets at the expense of corn starch (with basal protein content of 4.0 g/100 g sample) giving approximately the conventional 10% dietary protein (The United Nations University 1980).…”
Section: Formulation Of the Experimental Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a hygroscopic material with significant pores, moisture is transported to the unsaturated capillaries by sorption driven by gravity or surface capillary pressure and temperature‐dependent diffusion through the pores. This process involves soaking the fruits in warm water (warm press) at different temperatures and allowed for some time to soften (Anyalogbu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%